Implementasi Metode Naive Bayes Clasifier Untuk Klasifikasi Penyakit Periodontal Berdasarkan Data Pasien Pada Puskesmas Pajar Bulan - Sepriyanto Sepriyanto; Reno Supardi; Yessi Mardiana (UNIVED Press, 2025)
The purpose of this study is to apply the naïve bayes algorithm for the classification of periodontal disease at the Dental Polyclinic of the Pajar Bulan Health Center UPTD. Periodontal diagnosis is one of the diagnoses with severe conditions that are often complained about at the Dental Polyclinic of the Pajar Bulan Health Center UPTD. However, the problem at the Pajar Bulan Health Center UPTD is that the dental polyclinic patient data is still mixed in one book without any data grouping. So that it is difficult to determine the type or classification of periodontal disease according to its severity. Therefore, a method is needed that is able to classify the risk level of various periodontal diagnoses that occur at the Pajar Bulan Health Center UPTD so that they can be handled immediately with appropriate actions using the Naïve Bayes method. From the results of the tests carried out, the Naïve Bayes method can be used as a solution in using this system. In its application, this Naïve Bayes method can classify the type of periodontal disease at the Pajar Bulan Health Center UPTD